Caregiver Experiences of Care Coordination for Recently Discharged Patients: A Qualitative Metasynthesis. (August 2020) - Callister, Catherine; Jones, Jacqueline; Schroeder, Shara; Breathett, Khadijah; Dollar, Blythe; Sanghvi, Urvi Jhaveri; Harnke, Ben; Lum, Hillary D.; Jones, Christine D.
Caregivers of patients often provide key support for patients after hospitalization. This qualitative metasynthesis describes caregiver perspectives about care coordination for patients discharged from the hospital. A literature search of Ovid Medline and CINAHL completed on May 23, 2018, identified 1, 546 studies. Twelve articles were included in the final metasynthesis. Caregiver perspectives about care coordination were compiled into overall themes. A subanalysis of studies in which patients were discharged with home health services was completed. Five main themes emerged related to caregiver perspectives on care coordination after hospitalization: (a) Suboptimal access to clinicians after discharge, (b) Feeling disregarded by clinicians, (c) Need for information and training at discharge, (d) Overwhelming responsibilities to manage appointments and medications, and (e) Need for emotional support. Findings from this metasynthesis suggest the need for clinicians to engage with caregivers to provide support, training, and communication after hospital discharge.